Desarrollo de un sistema de gestión integral de los residuos sólidos generados en la parroquia Belisario Quevedo cantón Latacunga provincia de Cotopaxi periodo 2023. - Pullopaxi Yugla, Vanessa Anabel (2023)
This project was carried out in the parish of Belisario Quevedo, Latacunga canton, whose main objective is to develop an Integral Management System for Solid Waste Management. To develop the research work, the general diagnosis of the current management of solid waste in the parish was based, applying the survey method together with the observation technique, it was possible to identify the main problems and needs of the inhabitants. Subsequently, the calculation and fieldwork phase was carried out to determine the analysis and results of the characterization of household waste. The characterization was carried out with a total of 70 samples distributed in the areas of the parish, during 7 consecutive days where through the methodology proposed by Dr. Kunitoshi Sakurai and Cantanhede, "Guide for the characterization of household solid waste" developed by CEPIS and PAHO, the PPC generation (Per capita) and the physical composition of solid waste were determined by the quarting method. The results obtained in the parish show that there is currently a per capita production of 0.47 kg / inhabitant / day. The percentages obtained in the composition of waste were 42% organic matter, 52% recyclable inorganic matter and 1% special waste. Finally, it was determined that the Integrated Waste Management System covers most of the population, however there are sectors that still maintain deficiencies and it is important to take into account research to optimize the effectiveness of the service. Based on the results obtained, from this the proposal of a plan of integral management of solid waste is proposed, on which the parish GAD of Belisario Quevedo will be in charge of implementing it, proposing alternatives such as, solid waste storage, collection and transport, training, environmental education, use of solid waste, occupational health and safety these programs contain their activities respectively and will contribute to Improve the integral management of solid waste generated in the parish.